Hungary : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation for Hungary highlights that developments in growth and inflation were broadly positive in 2002. Buoyed by domestic demand, real GDP growth increased to 3.5 percent (year-over-year) in the second half of 2002 from 3.0 percent in the first half. Headline inflation declined from its recent peak of 10.8 percent in May of 2001 to 4.8 percent at end-2002. The external current account deficit widened in 2002, although foreign direct investment fell off sharply.